2020
DOI: 10.1007/s00127-020-01846-4
|View full text |Cite
|
Sign up to set email alerts
|

Educational attainment in offspring bereaved by sudden parental death from external causes: a national cohort study from birth and throughout adulthood

Abstract: Purpose Previous research has linked loss of a parent during childhood to reduced educational aspirations, school performance, and educational attainment later in life. The potential effect of maternal and paternal bereavement on attainment at all educational levels is, however, unknown. The present study aimed to investigate the potential influence of parental death by external causes on completion of compulsory education, high school, vocational education, and University or College education. Methods The stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 35 publications
5
20
0
1
Order By: Relevance
“…Results from the present study reporting an increased risk of DSH hospitalization in bereaved offspring are consistent with prior Scandinavian register studies [5,[10][11][12][13][14][15]17], and add to the literature, suggesting that many bereaved offspring in Norway suffer from extensive psychosocial sequela [6,7]. The explanation for the increased risk following bereavement may to a certain degree lie in the covariates included in the study, since the associations were attenuated in the multivariate analyses and all covariates significantly predicted DSH hospitalization.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Results from the present study reporting an increased risk of DSH hospitalization in bereaved offspring are consistent with prior Scandinavian register studies [5,[10][11][12][13][14][15]17], and add to the literature, suggesting that many bereaved offspring in Norway suffer from extensive psychosocial sequela [6,7]. The explanation for the increased risk following bereavement may to a certain degree lie in the covariates included in the study, since the associations were attenuated in the multivariate analyses and all covariates significantly predicted DSH hospitalization.…”
Section: Discussionsupporting
confidence: 90%
“…Naturally, the children of the deceased are highly impacted by this loss given the broken attachment to a primary care giver [3] and the direct effect of loss on daily life [4]. The sudden death of a parent is consequently associated with an increased risk of longterm psychosocial sequela [5][6][7], and several Scandinavian population-based register studies have reported an increased risk of hospital treatment for deliberate self-harm (DSH) in bereaved offspring [5,[8][9][10][11][12][13][14][15][16][17]. When directly comparing offspring bereaved by suicide and accidents, researchers have reported an earlier onset of DSH hospitalization in offspring following parental suicide compared to those parentally bereaved by accidental death [9].…”
Section: Introductionmentioning
confidence: 99%
“…Causes of death were classified according to the International Classification of Diseases (ICD-10) as (1) natural deaths (diseases) or deaths by external causes (accident, violence, or suicide [ICD-10 code: V01–Y89]). A similar classification was used in many other Nordic studies (e.g., Burrell et al, 2020 ; Berg et al, 2014 ; Rostila and Saarela, 2011 ). The parental death variables consisted of the following values: 0 alive (no parental death), 1 external death, 2 natural death, based on the primary causes of death, since the secondary causes were not available in the data.…”
Section: Methodsmentioning
confidence: 99%
“…Evidence on the cause of parental death and educational outcomes is based on a few studies, in which external deaths that are sudden or otherwise more traumatic, had the strongest associations with lower grades and a higher drop-out at compulsory school in Sweden ( Berg et al, 2014 ), and with impeded college or university enrolment in Taiwan ( Chen et al, 2009 ; Gimenez et al, 2013 ) and Norway ( Burrell et al, 2020 ). According to our knowledge, there are no studies that have examined the role of cause of parental death on early disability pension, which is an indicator of severely poor health and functioning.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation